Citrus Greening Disease Infection Reduces the Energy Flow Through Soil Nematode Food Webs - Mengqiang Wang; Zhilei Li; Jie Zhao (Agronomy)
Citrus greening disease (CGD), also known as Huanglongbing in China, is caused by the endophytic bacterium ‘Candidatus Liberibacter asiaticus’ and poses a severe threat to the global citrus industry. The disease affects microbial communities in leaves, stems, roots, and soil. Soil nematodes, which occupy multiple trophic levels, play crucial roles in nutrient cycling, pest regulation, and plant-soil interactions. However, the impact of CGD on soil nematode community structure and energy flow remains unclear. This study examined the effects of different levels of CGD infection on soil nematode communities and energy dynamics. Three infection levels were selected: control (healthy plants with no yellowing symptoms), mild infection (≤50% leaf yellowing), and severe infection (entire canopy affected). The results showed that increasing CGD severity significantly reduced the nematode abundance, community structure index, and total energy flux by 94.2%, 86.7%, and 93.5%, respectively, in the severely infected group. Both mild and severe infections resulted in a higher proportion of bacterivorous nematodes compared to the control. Moreover, herbivorous energy flux was significantly reduced by 99.2% in the severe infection group, suggesting that herbivorous endophytic nematodes are particularly sensitive to CGD. The total energy flux through nematode food web, the energy flux through fungal or herbivorous channels, and the energy flow uniformity were positively correlated with the nematode structure index but negatively correlated with the nematode richness and evenness indices. Furthermore, the reduction in soil resource input (especially total nitrogen and total carbon) caused by CGD was the primary driver of the changes in nematode communities and energy flows. These findings highlight the destructive effects of CGD on soil ecosystems through bottom-up control. The CGD-induced obstruction of photosynthate transport primarily impacts phytophagous organisms and could also influence other trophic levels. To mitigate these effects and ensure healthy citrus production, future research should focus on early detection and effective CGD management strategies.